SUPERHERO-Boosting Confidence, Shaping Future - Yuhani, Yusof; Amirul Aizad, Ahmad Fuad (Pusat Sains Matematik (PSM), 2024)
On 10 December 2024, a special "SUPERHERO Course" took place at Dewan Al-Banna, Kuantan, aimed at motivating and inspiring the Ujian Penilaian Kelas KAFA 2024 (UPKK 2024) students from KAFA Al-Banna, Kuantan. The event, organised by the Centre for Mathematical Sciences of UMPSA in collaboration with Angkatan Belia Islam Malaysia (ABIM), Cawangan Pahang, and Al-Banna Centre, was designed to provide a boost of motivation for the students as they prepared for their upcoming UPKK 2024 exams.